Morphometric evaluation of relevant radiographic parameters of the forefeet of clinically normal donkeys (Equus αsinus) - EL-SHAFAEY, E. A.; SALEM, M. G.; MOSBAH, E.; ZAGHLOUL, A. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study provides a standard database of morphometric evaluation of the digital bone and hoof parameters of the forefeet of clinically normal donkeys using Digital Imaging and Communications in Medicine (DICOM) software programme, as a means to improve diagnosis and clinical decision-making regarding foot lameness in equine practice. Thirty orthopedically sound donkeys were included in this study. For each donkey forefoot, lateromedial (LM) and dorsopalmar (DP) radiographs were obtained with the foot in a vertical position. A total of 26 digital bone and hoof parameters obtained from the LM and DP radiographs were evaluated through repeated measurements of the same digitalized radiograph by three operators using DICOM software. Data of the morphometric radiographic parameters of the forefeet were statistically analyzed for the frequency distribution and calculation of the intra-assay and interassay coefficients of variation (CVs) of the reproducibility of the measured parameters. Mean ± SD of digital bone and hoof parameters were significantly different among the measurements obtained for the 26 parameters. However, intra-assay and interassay CVs for digital bone and hoof parameters measurements did not differ significantly between the three examiners. In conclusion, morphometric evaluation of the radiographic parameters of the forefeet in clinically normal donkeys, establishes a reference data base correspondingly for the donkey different to those accepted for the horse.